2018
DOI: 10.1128/iai.00135-18
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Surfactant Promotes Virulence Gene Expression and Biofilm Formation in Klebsiella pneumoniae

Abstract: The interactions between and the host environment at the site of infection are largely unknown. Pulmonary surfactant serves as an initial point of contact for inhaled bacteria entering the lung and is thought to contain molecular cues that aid colonization and pathogenesis. To gain insight into this ecological transition, we characterized the transcriptional response of MGH 78578 to purified pulmonary surfactant. This work revealed changes within the transcriptome that likely contribute to host colonization, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 114 publications
0
26
1
Order By: Relevance
“…2 and Table 1). We speculate that some of the "stress" imposed by SCFM2 is utilization of lipids and head-group moieties whose metabolic pathways generate endogenous stress, since similar responses are also seen for P. aeruginosa and Klebsiella pneumonia during exposure to lung surfactant (55,56), and by P. aeruginosa when exposed to choline and its metabolites (57). Furthermore, expression of amino acid and polyamine efflux pumps was shared between all three S. maltophilia strains, suggesting that growth in SCFM2 results in metabolic stress due to the accumulation of excess nitrogen, likely from amino acid (Fig.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…2 and Table 1). We speculate that some of the "stress" imposed by SCFM2 is utilization of lipids and head-group moieties whose metabolic pathways generate endogenous stress, since similar responses are also seen for P. aeruginosa and Klebsiella pneumonia during exposure to lung surfactant (55,56), and by P. aeruginosa when exposed to choline and its metabolites (57). Furthermore, expression of amino acid and polyamine efflux pumps was shared between all three S. maltophilia strains, suggesting that growth in SCFM2 results in metabolic stress due to the accumulation of excess nitrogen, likely from amino acid (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Transcription of the polyamine efflux pump genes, the predicted mdtJ and mdtI orthologs, increased several 100-fold under these conditions. The expression of mdtJI was recently shown to be important for K. pneumoniae survival in a mouse model of acute pneumonia (62). It is therefore plausible that the expression of this pump could similarly influence S. maltophilia fitness in the context of the CF lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specicity of cy(LLFFF) towards MrkA in particular was further interrogated by affinity tests to KPPR1 cells in which the gene encoding MrkA was knocked out (along with mrkB and mrkC). 64 Western blot analysis conrmed that this modied KPPR1 strain does not produce MrkA ( Fig. 5B inset, full blot in Fig.…”
Section: Ar-pcc Binding To Multidrug Resistant Klebsiella Pneumoniae mentioning
confidence: 92%
“…For example, in a mouse model of lung infection by Klebsiella pneumoniae, lysozyme M knockout mice did not survive beyond 72 h post infection, whereas 25% of wild-type mice survived up to 120 h (Markart et al, 2004). Transcriptomic analysis of K. pneumoniae exposed to pulmonary surfactant showed that relative to controls, interaction with lung secretions increased ybiS LD-transpeptidase expression (Willsey et al, 2018). Upregulation of ybiS expression may be part of a general envelope stress response, similar to the increase of E. coli ldtD transcription during the Cpx envelope stress response (Bernal-Cabas et al, 2015); alternatively, it may be a specific program for modulating peptidoglycan composition to avoid killing by the host lysozyme defense.…”
Section: Ld-transpeptidation Increases Lysozyme Resistancementioning
confidence: 99%